(3QSGdI aj GdbQBf heG hbY ajg ef GdfRGY hHjGf GdMbs - (3CMeO Hf YHO GdMdje Hf YHO GdSdGe GdMQGfj, Jbj GdOjf, GHf JjejI, CHh GdYHGS , J (B728 (3g` s ((3YHOGdefGf GdcGHdj s)
(3ChdgG (B:s
(3oSFd GdTjN Yf QLdjf JHGMKG abGd CMOgeG GdbQBf MQa hUhJ hbG GdBNQ djS HMQa hdGUhJ s
(3BNQgG (B:s
(3hgPg GdCehQ eHShWI aj ZjQ gPG GdehVY hbO HSWfG aj GdhGLH GdcHjQ hGddg CYde HGdUhGH hGdMeO ddg hMOg Je GdLhGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B27s
(3GdfSNI HgG MhGTs
(3QSGdI aj GdJhMjOs
(3hQOJ CjVkG JMJ Qbe (B/430 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B261s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds